Is sex a biological variable in corneal wound healing?. (October 2019) - Tripathi, Ratnakar; Giuliano, Elizabeth A.; Gafen, Hannah B.; Gupta, Suneel; Martin, Lynn M.; Sinha, Prashant R.; Rodier, Jason T.; Fink, Michael K.; Hesemann, Nathan P.; Chaurasia, Shyam S.; Mohan, Rajiv R.
Abstract: Wound healing differs significantly between men and women in a tissue-dependent manner. Dermal wounds heal faster in women whereas mucosal wounds heal faster in men. However, the effect of sex as a variable in corneal wound healing is largely unknown. The primary objective of this study was to test whether sex is a biological variable in corneal wound healing activated by the trauma or injury using an established in vivo rabbit model with male and female New Zealand White rabbits. Corneal wounds in rabbits were produced by a single topical alkali (0.5N Sodium hydroxide) application. Serial slit-lamp, stereo biomicroscopy, and applanation tonometry evaluated corneal opacity, anterior segment ocular health, and intraocular pressure (IOP), respectively, at various times during the study. Fourteen days after alkali-wound, corneal tissues were collected after humane euthanasia to examine cellular and molecular wound healing parameters. Quantitative PCR (qPCR) and immunofluorescence were used to quantify changes in the extracellular modeling protein levels of alpha-smooth muscle actin (α-SMA), Fibronectin (FN), Collagen-I (Col-I), and Transforming growth factor beta 1 (TGFβ1) involved in corneal healing. Hematoxylin and Eosin (H&E) staining was used to study histopathological changes in morphology and TUNEL assay to evaluate levels of apoptotic cell death. Male and female rabbits showed no significant differences in corneal opacity (Fantes score) or intraocular pressure (IOP) values (9.5 ± 0.5 mm Hg) in live animals. Likewise, no statistically significant sex-based differences in the mRNA levels of α-SMA (male = 5.95 ± 0.21 fold vs. female = 5.32 ± 0.043), FN (male = 3.02 ± 0.24 fold vs. female = 3.23 ± 0.27), Col-I (male = 3.12 ± 0.37 fold vs. female = 3.31 ± 0.24), TGFβ1 (male = 1.65 ± 0.06 fold vs. female = 1.59 ± 0.053); and protein levels of α-SMA (male = 74.16 ± 4.6 vs. female = 71.58 ± 7.1), FN (male = 60.11 ± 4.6 vs. female = 57.41 ± 8.3), Col-I (male = 84.11 ± 2.8 vs. female = 84.55 ± 3.6), TGFβ1 (male = 11.61 ± 2.8 vs. female = 9.5 ± 3.04) were observed. Furthermore, H&E and TUNEL analyses found no statistically significant differences in cellular structures and apoptosis, respectively, in male vs. female corneas. Consistent with earlier reports, wounded corneas showed significantly increased levels of these parameters compared to the unwounded corneas. Our data suggest that sex is not a major biological variable during active early stages of corneal wound healing in rabbits in vivo . Highlights: Sex is a key biological variable in a tissue-specific manner but its role in corneal wound healing is currently unknown. Comparative analysis of corneal wound healing parameters showed no significant differences in male versus female rabbits. Sex does not appear a major variable in active corneal wound healing in vivo triggered after trauma/injury